Digging up Jericho : past, present and future - Sparks, Rachael Thyrza; Finlayson, Bill; Wagemakers, Bart; Briffa, Josef Mario (Archaeopress archaeology., 2019)
Digging Up Jericho: Past Present and Future, arising from a conference exploring the heritage, archaeology and history of the Jericho Oasis, includes contributions by 21 internationally significant scholars. Once dubbed the 'Oldest City in the World', Jericho has been the focus of intense archaeological activity and media interest in the 150 years since its discovery. From early investigations in the 19th century, through Kathleen Kenyon's work at the site in the 1950s, to the recent Italian-Palestinian Expedition and Khirbat al-Mafjar Archaeological Project, Jericho and its surrounding landscape has always played a key role in our understanding of this fascinating region. Current efforts to get the site placed on the World Heritage List only enhance its appeal. Covering all aspects of work at the site, this volume offers the opportunity to re-evaluate and assess the legacy of this important site.